Growth and yield of coriander (Coriandrum sativum L) as influenced by irrigation and nutrient levels with varying crop geometry - Mehta, RS; Lal, G; Vishal, MK (Annals of Agricultural Research, 2014)
Field experiment was conducted during rabi season of 2003-06 at NRCSS, Ajmer (Rajasthan) to study the growth, profitability and productivity of coriander (Coriandrum sativum L) as influenced by irrigation and nutrient levels with varying crop geometry. Three irrigation levels (12, 15 and 18 days interval) in main plot, nutrient levels (N and P2O5 each of 30 +15 , 40+20 and 50+25 kg/ha, respectively) in sub plot and crop geometry ( 20 x 10, 25 x 10 and 30 x 10 cm ) in sub-sub plot were studied in split-plot design with three replications. The highest plant height at all the growth stages, branches /plant, dry matter accumulation/plant at 80 DAS and harvest of coriander were recorded with application of irrigation at 15 days interval but higher dry matter /plant at 40 DAS was obtained with irrigation at 18 days interval. Yield attributes, seed yield (12.12 q/ha) and straw yield (18.43 q/ha) was recorded with irrigation at 15 days interval and remained at par with 18 days interval but the highest net return (Rs 41,565/ha) and B:C (2.27) was obtained with 18 days irrigation interval. The higher growth parameters, yield attributes, seed yield (12.48 q /ha), net return (Rs. 42,922/ha) and B:C (2.21) were obtained with application of 50 kg N and 25 kg P2O5 /ha. Crop geometry 30 x 10 cm resulted 9 % higher seed yield over 20 x10 cm. Thus, application of irrigation at 15 days interval with 50 kg N + 25 kg P2O5/ha at 30 x 10 cm crop geometry is better for realizing higher yields but higher net return and profitability in coriander production may be realized with application of irrigation at 18 days interval.